Analysis of Leukocyte Behaviors on Microfluidic Chips. Issue 4 (23rd January 2019) - Liu, Yan; Yang, Qingzhen; Cao, Lei; Xu, Feng
Abstract: The orchestration of massive leukocytes in the immune system protects humans from invading pathogens and abnormal cells in the body. So far, researches focusing on leukocyte behaviors are performed based on both in vivo and in vitro models. The in vivo animal models are usually less controllable due to their extreme complexity and nonignorable species issue. Therefore, many researchers turn to in vitro models. With the advances in micro/nanofabrication, the microfluidic chip has emerged as a novel platform for model construction in multiple biomedical research fields. Specifically, the microfluidic chip is used to study leukocyte behaviors, due to its incomparable advantages in high throughput, precise control, and flexible integration. Moreover, the small size of the microstructures on the microfluidic chip can better mimic the native microenvironment of leukocytes, which contributes to a more reliable recapitulation. Herein are reviewed the recent advances in microfluidic chip–based leukocyte behavior analysis to provide an overview of this field. Detailed discussions are specifically focused on host defense against pathogens, immunodiagnosis, and immunotherapy studies on microfluidic chips. Finally, the current technical challenges are discussed, as well as possible innovations in this field to improve the related applications. Abstract : Microfluidic chips have greatly promoted immunological studies due to their advantages in microenvironment recapitulation, fluid control, and real‐time imaging. They serve as excellent models in the analysis of leukocyte behaviors, including leukocyte priming, migration, and cellular interactions. Here, recent advances in microfluidic chip–based leukocyte behavior studies are reviewed with special focus on host defense, immunodiagnosis, and immunotherapy.